The Role of Islamic Religious Education Teachers in the Dual System of Schools and Islamic Boarding Schools: A Qualitative Study on Integrating Formal Values and Pesantren Traditions - M. FIrmansyah; Ahmad Hafis Taufiqi (Al Yazidiy Jurnal Sosial Humaniora dan Pendidikan, 2026)
This study aims to analyze the role of Islamic Education (PAI) teachers in the dual system of school and Islamic boarding school (pesantren), particularly in integrating formal educational values with pesantren traditions. This research employs a qualitative approach with a case study design conducted in a pesantren-based educational institution. Data collection techniques include observation, in-depth interviews, and documentation. The findings reveal that PAI teachers play a strategic role as value mediators, learning facilitators, and role models in harmonizing formal curricula with pesantren culture. This integration is reflected in the learning process, religious habituation, and the internalization of moral values in students’ daily lives. However, several challenges were identified, including differences in pedagogical approaches, time constraints, and students’ adaptation to the dual system. This study contributes to the development of an integrative educational model that bridges academic and spiritual needs of students.